Political theology of the earth: our planetary emergency and the struggle for a new public - Keller, Catherine (Insurrections: critical studies in religion, politics, and culture, 2018)
Political : sovereign exception or collective inception -- Earth : climate of closure, matter of disclosure -- Theology : "unknow better now